Comparison of selected clinical and personality variables in alcohol–dependent patients with or without a history of suicide attempts - Gerhant, Aneta; Krzewicka-Romaniuk, Ewa; Siedlecka, Dagna; Derewianka-Polak, Magdalena; Olajossy, Marcin (Current Problems of Psychiatry, 2018)
Objective: The aim of the study was to determine differences in the range of socio-demographic variables, selected clinical variables, temperament and character traits, coping with stress strategies and the level of aggression in alcohol addicts with or without a history of suicide attempt(s). Methods: The study involved 90 people addicted to alcohol, treated in inpatient alcohol dependence treatment program. In order to collect data on socio - demographic variables and selected clinical variables, a self-made questionnaire was used. The severity of alcohol dependence was verified using the MAST and SADD scales. Characteristics of temperament and character were examined with the TCI questionnaire. The BPAQ and COPE questionnaires were used to examine the level of aggression and styles of coping with stress. Results: Out of 90 subjects with alcohol dependence syndrom, 20% had attempted suicide in the past. The respondents with a history of suicide attempts were statistically significantly younger, were characterized by a younger age of alcohol drinking initiation and the initiation of regular alcohol drinking, and a greater severity of alcohol dependence in the MAST and SADD scales. A significantly larger percentage of respondents who had attempted suicide inflicted self-injury in the past, used other psychoactive substances as well as hypnotics and sedatives. The subjects with a suicide attempt in the interview obtained statistically significantly higher scores in terms of the level of aggression, harm avoidance and self-directedness, and more often used the style of coping with stress based on avoidance and accepting the situation. Conclusions: The obtained results correspond with data available in the literature and may provide a foundation for theoretical models explaining the phenomenon of suicidal behavior in alcohol addicts as well as for suicide prevention programs in this group of patients.